Emissions and Air Quality Implications of Upstream and Midstream Oil and Gas Operations in Mexico - Elena McDonald-Buller; Gary McGaughey; John Grant; Tejas Shah; Yosuke Kimura; Greg Yarwood (Atmosphere, 2021)
Mexico approved amendments to its constitution in December 2013 that initiated transformational changes to its energy sector. This study developed a 2016 bottom-up emissions inventory for volatile organic compounds (VOCs), nitrogen oxides (NOx), sulfur dioxide (SO2), carbon monoxide (CO), and fine particulate matter (PM2.5) from upstream and midstream sector sources, including onshore and offshore well sites, gas flaring, natural gas processing facilities, and natural gas compressor stations, throughout Mexican basins. Crude oil storage tanks at onshore oil well sites and venting and fugitive sources at offshore oil production sites were the primary sources of VOC emissions. Key contributions to NOx, CO, and PM2.5 emissions were from internal combustion engines at offshore oil well sites and midstream operations. SO2 emissions were associated with onshore and offshore gas flaring and boilers and process heaters at natural gas processing facilities. Application of the inventory with the Comprehensive Air Quality Model with Extensions (CAMx) indicated that oil and gas production operations could contribute to ozone and PM2.5 concentrations in Mexican and U.S. states under favorable transport patterns. This study provides a foundation for assessing the implications of Mexico’s future energy policies on emissions and domestic and cross-border air quality and public health.